Statistical estimation of wear in permanent teeth: A systematic review - Akeem A. Azeez; Sherif Sherif; Rodrigo França (Elsevier, 2021)
Objectives: An up to date quantitative assessment of the prevalence of tooth wear (with dentine exposure) in permanent dentition is lacking. The purpose of this systematic review was to synthesize clinical studies and research related to tooth wear in order to derive an overall estimate of the prevalence of tooth wear in permanent dentition. Data/sources: The eligibility criteria used in his work included population-based studies that reported the prevalence of tooth wear in permanent teeth of both adolescents and adults aged 12-80-year-old. Following the eligibility criteria, an electronic search of databases- Medline, Scopus, Embase and Science Citation Index and Biosis (Web of Science)-were performed from 1984 to 2020. Data regarding the sample size, geographical locations, year of publication, age etc. were extracted from each study and the overall estimated prevalence of tooth wear was determined. Meta-regression analysis was used to determine the source of heterogeneity in the studies while Bhattacharyya Distance (BD) was deployed to investigate the relationship within the source of the heterogeneity. Study selection: The search strategy identified 4205 studies and after removal of duplicates (959), title and abstract screening (3206) and full-text reading (60), 22 studies comprising of total 20,112 subjects were included in the systematic review. The overall estimated prevalence of the tooth wear was 38% (95% CI: 31-46%), the subgroup meta-analysis revealed that continents (region) of publications was responsible for the variability of the prevalence of tooth wear within the included studies with Europe having the least prevalence rate. Bhattacharyya Distance (BD) highlighted that studies from Africa were remarkably different from other studies, whereas studies from Europe, America and Asia share some similarities. Conclusions: We showed that the prevalence of tooth wear with dentin exposure was 38%, with significant heterogeneity between the included studies, and the variability depends mostly on the geographical location of the studies. Clinical significance: The results of this study can be used as an information guide by clinicians and policymakers to know the global tooth wear prevalence; can be used as a conductor in formulating policies that will help in reducing the tooth wears.